2017
DOI: 10.17977/um022v2i12017p031
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Sosial Perkawinan Di Bawah Umur Bagi Kehidupan Masyarakat Desa Kunjorowesi Kecamatan Ngoro Kabupaten Mojokerto

Abstract: AbstrakDi Desa Kunjorowesi Kecamatan Ngoro Kabupaten Mojokerto sangat banyak yang melakukan pernikahan di bawah umur, dari data awal yang peneliti dapatkan sebelum penelitian ini dilakukan salah satu sumber informasi atau informan mengatakan dilihat dari segi pendidikan saja, banyak anak lulusan SD khususnya pelajar perempuan banyak yang tidak melanjutkan ke jenjang SMP dengan alasan membantu orang tua dan dinikahkan oleh orang tuanya, dari data tersebut saja dapat dilihat bahwa kesadaran yang sangat rendah da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study found that one third (34.1%) of responsive pregnant women had low education, almost all (88%) did not work for income, and (83.7%) had low household income and resulted in low health literacy, especially viarabel the ability to obtain access to information as a main condition for health literacy. A mother's endogeneity and health status is more due to lack of knowledge, education, and income [13]. There is a significant relationship between education, knowledge, and income with the ability of maintenance and prevention health in inbu at each p = 0.000; 0.016; and 0.004) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that one third (34.1%) of responsive pregnant women had low education, almost all (88%) did not work for income, and (83.7%) had low household income and resulted in low health literacy, especially viarabel the ability to obtain access to information as a main condition for health literacy. A mother's endogeneity and health status is more due to lack of knowledge, education, and income [13]. There is a significant relationship between education, knowledge, and income with the ability of maintenance and prevention health in inbu at each p = 0.000; 0.016; and 0.004) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of early marriage is common in Indonesia. This has been happening for a long time in several regions scattered in parts of Indonesia, especially in rural and rural areas [1]. With a variety of backgrounds such as social, economic, and cultural [2].…”
Section: Introductionmentioning
confidence: 99%